Positive Group Context, Work Attitudes, and Organizational Misbehavior: The Case of Withholding Job Effort - Kidwell, Roland E. (Journal of business ethics, 2009)
Considering the organization’s ethical context as a framework to investigate workplace phenomena, this field study of military reserve personnel examines the relationships among perceptions of psychosocial group variables, such as cohesiveness, helping behavior and peer leadership, employee job attitudes, and the likelihood of individuals’ withholding on-the-job effort, a form of organizational misbehavior. Hypotheses were tested with a sample of 290 individuals using structural equation modeling, and support for negative relationships between perceptions of positive group context and withholding effort by individual employees was found. In addition, individual effort-performance expectancy and individual job satisfaction were negatively related to withholding effort. The findings provide evidence that individual perceptions of positive group context play a key role in the presence of misbehavior at work. The results indicate that positive group context might be an important element of ethical climate that should be managed to temper occurrence of such adverse work behavior.